2023
DOI: 10.1101/2023.08.26.554955
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Functional Organization of Glycolytic Metabolon on Mitochondria

Haoming Wang,
John Vant,
Youjun Wu
et al.

Abstract: Glucose, the primary cellular energy source, is metabolized through glycolysis initiated by the rate-limiting enzyme Hexokinase (HK). In energy-demanding tissues like the brain, HK1 is the dominant isoform, primarily localized on mitochondria, crucial for efficient glycolysis-oxidative phosphorylation coupling and optimal energy generation. This study unveils a unique mechanism regulating HK1 activity, glycolysis, and the dynamics of mitochondrial coupling, mediated by the metabolic sensor enzyme O-GlcNAc tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 93 publications
(155 reference statements)
0
3
0
Order By: Relevance
“…Ara-C-containing medium was replaced with fresh neuron maintenance medium at 5 DIV. The primary neuron cultures were maintained for 12-15 days in vitro by replacing one-third of the culture medium with a fresh medium every three days 14,15 . For respirometry measurements, the neuronal maintenance medium was exchanged with XF DMEM Base Medium (pH 7.4) with no phenol red (Agilent) supplemented with 5 mM glucose and 1 mM pyruvate.…”
Section: Methodsmentioning
confidence: 99%
“…Ara-C-containing medium was replaced with fresh neuron maintenance medium at 5 DIV. The primary neuron cultures were maintained for 12-15 days in vitro by replacing one-third of the culture medium with a fresh medium every three days 14,15 . For respirometry measurements, the neuronal maintenance medium was exchanged with XF DMEM Base Medium (pH 7.4) with no phenol red (Agilent) supplemented with 5 mM glucose and 1 mM pyruvate.…”
Section: Methodsmentioning
confidence: 99%
“…This modification enhances the mitochondrial binding of HK1, coordinating glycolysis and mitochondrial ATP production. Mutations in the O-GlcNAcylation site of HK1 reduce ATP production [10]. He et al reported that the IDH2 protein was highly expressed in colorectal cancer tissues (CRC) and correlated with poor survival in CRC patients.…”
Section: Mitochondrial Energy Metabolismmentioning
confidence: 99%
“…The adaptive regulation of energy disturbances in the O-GlcNAc cycle has been shown to be crucial for maintaining mitochondrial homeostasis [5,6]. The imbalance of O-GlcNAcylation in mitochondria is related to various mitochondrial dysfunctions, such as abnormal mitochondrial dynamics, decreased mitochondrial biosynthesis, disruption of electron transport chains (ECTs), oxidative stress and the calcium paradox and mitophagy, as well as the activation of mitochondrial apoptosis pathways [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%